2016
DOI: 10.3233/jpd-160921
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibition Model of Parkinson’s Disease

Abstract: The pathological hallmarks of Parkinson’s disease are the progressive loss of nigral dopaminergic neurons and the formation of intracellular inclusion bodies, termed Lewy bodies, in surviving neurons. Accumulation of proteins in large insoluble cytoplasmic aggregates has been proposed to result, partly, from a failure in the function of intracellular protein degradation pathways. Evidence in support for such a hypothesis emerged in the beginning of the years 2000 with studies demonstrating structural and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 213 publications
2
79
0
Order By: Relevance
“…Rodent models of PD have been generated using inhibitors of the UPS -a detailed review of these models can be found in Bentea et al (2017). One such inhibitor is lactacystin, which spontaneously undergoes hydrolysis to the more potent inhibitor clasto-lactacystin-β-lactone (Dick et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Rodent models of PD have been generated using inhibitors of the UPS -a detailed review of these models can be found in Bentea et al (2017). One such inhibitor is lactacystin, which spontaneously undergoes hydrolysis to the more potent inhibitor clasto-lactacystin-β-lactone (Dick et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…While two previous studies determined that NAC can shield astrocytes from b-amyloid toxicity (Brera et al, 2000;de Ceballos et al, 2001), it is unknown whether NAC also protects astrocytes against the severe loss of protein quality control associated with proteasome inhibition. To address this gap, we employed the proteasome inhibitor MG132, which has been used to elicit loss of dopaminergic cells and model Parkinson's disease in vivo (Sun et al, 2006;Lu et al, 2010;Xie et al, 2010;Bentea et al, 2017). Clasto-lactacystin b-lactone and MG132 have been applied in vivo to study the role of the ubiquitin-proteasome system in a-synuclein degradation (Ebrahimi-Fakhari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The proteasome system, which plays a central role in degrading dysfunctional proteins, has been shown to be impaired in the postmortem substantia nigra (SN) of PD patients (Bentea et al, 2017). Exposure to the proteasomal inhibitor carbobenzoxyl-L-leucyl-L-leucyl-L-leucine (MG-132) determined a higher susceptibility in PD patients' cells (Nguyen et al, 2011;Lin et al, 2016).…”
Section: Stressor Responsementioning
confidence: 99%